Sex hormones in men with normal or increased body weight and stable or unstable angina - V. A. Nevzorova; O. V. Nastradin; E. S. Potapova (Кардиоваскулярная терапия и профилактика)
Aim. То assess serum levels of sex hormones in men with normal or increased body weight (BW) and stable or unstable angina (SA, UA).Material and methods. Sixty-three men aged 30—45 years were divided into two groups: Group I (n=33) — with coronary heart disease (CHD) and Functional Class (FC) I-II SA; Group II (n=30) — CHD patients with UA. Serum levels of sex hormones were measured by immuno-enzyme methods; all participants also underwent anthropometry.Results. Statistically significant increase in visceral fat tissue volume (VFTV), together with testosterone (T) level reduction, was observed in CHD men with both normal or mildly increased BW.Conclusion. In all groups, T levels were significantly lower than in controls. CHD was characterized by dysregulation of T and luteotropin levels, especially in patients with increased BW. VFTV was associated with reduced T concentration via T conversion into estradiol in abdominal fat tissue.